Exploring employee selection procedures in South African organisations - Juliet I. Townes; Tatenda S. Marange; Molefe J. Maleka (SA Journal of Human Resource Management)
Orientation: Using appropriate selection procedures assists organisations in acquiring applicants with the right competencies, a positive attitude and alignment with organisational values, providing a competitive advantage in the market.